2020
DOI: 10.1186/s41938-020-00300-6
|View full text |Cite
|
Sign up to set email alerts
|

Larval feeding capacity and pollination efficiency of the aphidophagous syrphids, Eupeodes frequens (Matsmura) and Episyrphus balteatus (De Geer) (Diptera: Syrphidae) on the cabbage aphid (Brevicoryne brassicae L.) (Homoptera: Aphididae) on mustard crop

Abstract: The present investigation was carried out on in vitro mass multiplication, larval feeding capacity, and pollination efficiency of two aphidophagous syrphids viz., Eupeodes frequens (Matsmura) and Episyrphus balteatus (De Geer) (Diptera: Syrphidae) on cabbage aphid (Brevicoryne brassicae L.) (Homoptera: Aphididae) on mustard crop under mid hill conditions. The results revealed that the incubation, larval, and pupal periods were 3.5, 12.4, and 11.9 days, respectively for E. frequens and 3.8, 13.7, and 8.8 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This result agrees with Hong and Hung [ 57 ], who demonstrated the influence of the temperature on the lifespan of the syrphid E. balteatus . In some syrphids species, it has been observed that the female lives longer (2 days more) than the male [ 25 ], and this was confirmed by our results. The females of S. rueppellii live (25 ± 0.93 days) compared to males (23.4 ± 093 days), although no significant differences were found.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result agrees with Hong and Hung [ 57 ], who demonstrated the influence of the temperature on the lifespan of the syrphid E. balteatus . In some syrphids species, it has been observed that the female lives longer (2 days more) than the male [ 25 ], and this was confirmed by our results. The females of S. rueppellii live (25 ± 0.93 days) compared to males (23.4 ± 093 days), although no significant differences were found.…”
Section: Discussionsupporting
confidence: 91%
“…An exception is E. balteatus , a common Palearctic hoverfly, of great importance as a natural enemy [ 6 , 18 , 22 , 23 , 24 ]. In this species, adult feeding affects longevity [ 25 ] and oviposition [ 24 , 26 ]. In addition, the presence of oviposition stimuli directly affects the maturation of the ovaries, the number of eggs produced, and the absorption of the eggs [ 22 , 23 , 27 ], but nothing is known about the sexual maturation of the males.…”
Section: Introductionmentioning
confidence: 99%
“…Similar study conducted by Deuri et al (2018) on mango inflorescence revealed that foraging rate of A. cerana indica was maximum (11.64) at 0900-1000 hr and minimum (3.49) at 1300-1400 hr. Singh et al (2018) also reported that maximum foraging rate (10.86) was recorded at 1200-1300 hr and minimum (6.37) at 0900-1000 hr. The time spent by A. cerana indica (6.24 sec/ flower) and T. iridipennis (6.20) on aonla flowers were recorded maximum at 1100-1200 hr and lower values (2.42 and 3.04) were observed at 1700-1800 hr.…”
Section: Resultsmentioning
confidence: 88%
“…As larvae, syrphids are efficient predators of aphids and have been used for biological control in agriculture (Bugg et al, 2008; Curran, 1920; Hopper et al, 2011). As adults, syrphids are pollinators of plants such as mustards (Singh et al, 2020), strawberries (Sharma et al, 2014) and many wildflowers (Tooker et al, 2006). Wild bees are also important pollinators of many crops such as alfalfa (Pitts‐Singer & Cane, 2011), blueberries (Blaauw & Isaacs, 2014; Isaacs & Kirk, 2010), cherries (Holzschuh et al, 2012) and sunflowers (Greenleaf & Kremen, 2006).…”
Section: Introductionmentioning
confidence: 99%